2020
DOI: 10.22336/rjo.2020.45
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ocular aberrations in three types of rigid gas permeable lenses in keratoconus patients

Abstract: Purpose: To determine the effect of different types of Rigid Gas Permeable (RGP) contact lenses on ocular aberrations in patients with keratoconus. Methods: Eighteen eyes of young patients with mild to moderate keratoconus were selected. General ocular examinations such as refraction, visual acuity, and ocular aberrations were performed. Three types of RGP contact lenses, i.e., Boston, Senso Select and Wohlk, were fitted using the cross over method. Repeated measures analysis of variance and Mauchly's test of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
1
3
Order By: Relevance
“…was greater than that observed with soft lenses in this study. However, the improvement in the total RMS was greater with the soft lenses used here, compared with Torkman et al 30 …”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…was greater than that observed with soft lenses in this study. However, the improvement in the total RMS was greater with the soft lenses used here, compared with Torkman et al 30 …”
Section: Discussioncontrasting
confidence: 57%
“…Further, in an investigation that examined the improvement in HOA with three types of RGP lenses in 18 eyes of keratoconic participants using a Hartmann-Shack device, mean improvements in vertical coma of 0.35, 0.37 and 0.39 μ were reported. 30 The improvement in coma with RGP lenses reported by Torkman et al 30 was greater than that observed with soft lenses in this study. However, the improvement in the total RMS was greater with the soft lenses used here, compared with Torkman et al 30 Differences between these findings may be attributed to use of varying instruments and lens designs.…”
Section: Unccontrasting
confidence: 44%
See 2 more Smart Citations